1999
DOI: 10.1258/0956462991913420
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Markers of Frequently Recurrent Genital Herpes Simplex Virus and Their Response to Hypnotherapy: A Pilot Study

Abstract: Patients were recruited for hypnotherapy from a clinic for patients with frequently recurrent genital herpes simplex virus (rgHSV). Psychological and immunological parameters were measured 6 weeks prior to hypnotherapy and 6 weeks afterwards, during which time each patient kept a diary of symptoms of rgHSV. Following hypnotherapy there was a significant overall reduction in the number of reported episodes of rgHSV, accompanied by an increase in the numbers of CD3 and CD8 lymphocytes, which may represent a non … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 23 publications
0
9
0
1
Order By: Relevance
“…Accordingly stress-control psychological interventions appear to have a place in the treatment of HIV. Indeed, self-hypnosis training was found to be highly effective in ameliorating a chronic viral infection, HSV-2, in patients in whom it was not only chronic, but highly virulent; recurrence rate was reduced by half with only six weeks of training (Fox, Henderson, Barton et al, 1999). However, psychological interventions are usually provided to treat psychological symptoms or pain (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Accordingly stress-control psychological interventions appear to have a place in the treatment of HIV. Indeed, self-hypnosis training was found to be highly effective in ameliorating a chronic viral infection, HSV-2, in patients in whom it was not only chronic, but highly virulent; recurrence rate was reduced by half with only six weeks of training (Fox, Henderson, Barton et al, 1999). However, psychological interventions are usually provided to treat psychological symptoms or pain (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In a series of studies on medical students in both the UK and the USA, students experiencing stress showed immunosuppression which was buffered by interventions including hypnosis (Kiecolt-Glaser, Glaser, Strain, Stout, Tarr, Holliday and Speicher, 1986;Glaser, Rice, Speicher, Stout and Kiecolt-Glaser, 1986;Gruzelier, Smith, Nagy and Henderson, 2001b;Naito, Laidlaw, Henderson, Farahani, Dwivedi and Gruzelier, 2003). An important component of treatment has been guided imagery, mostly in the context of hypnosis, which has been a technique used clinically with some research backing for its efficacy (Fox, Henderson, Barton, Champion, Rollin and Catalan, 1999;Gruzelier, Levy, Williams and Henderson, 2001a;Gruzelier, 2002a). In the Gruzelier et al (2001b) study, groups having immune imagery were directly compared to those having hypnosis without immune imagery and a control group (Gruzelier et al, 2001a).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The hypothesised health benefits were validated and were next explored in 20 patients with recurrent genital Herpes simplex virus (rgHSV) who were given six weeks of self-hypnosis training with directed imagery. Following hypnosis there was a 48% reduction in reported episodes accompanied by an increase in the numbers of CD3 and CD8 counts (Fox et al, 1999). 65% of patients improved in whom there was an increase in NKC counts, HSV specific LAK activity and reduced levels of anxiety.…”
mentioning
confidence: 95%